Assessment of Digitalization of Interaction Between the State and Citizens - E. I. Dobrolyubova; A. N. Starostina (Статистика и экономика)
The purpose of this paper is to develop a comprehensive approach to evaluating digitalization of interaction of the state and citizens in the sphere of providing state services. The objectives of the study include the analysis of current Russian and foreign approaches to assessing the digitalization of interaction between the state and citizens; development and testing of a composite indicator methodology for conducting such an assessment in the provision of public services. Materials and methods. When preparing the paper, the authors studied Russian and foreign theoretical and practical approaches to evaluating digitalization of interaction between the state and citizens. The approbation of the digitalization index of interaction between the state and citizens proposed in the article was carried out on the basis of data from a selective federal statistical observation of the Federal State Statistics Service on the use of information technologies, information and communication networks by the population, as well as the data from the Ministry of Economic Development of the Russian Federation. To achieve the objective, theoretical methods (comparative analysis, synthesis, and generalization), modelling, and correlation analysis were used. Results. Based on the analysis of foreign and Russian approaches, their advantages and limitations, the article substantiates the methodology for calculating the digitalization index of interaction between the state and citizens, taking into account the immediate results (the availability of state and municipal services in the electronic form), intermediate results (the demand for the electronic form of service provision) and the final results of digital transformation in the provision of public services (satisfaction of citizens with the quality of services provided in the electronic form), as well as the risks of digital interaction (the level of digital trust of citizens in the interaction with the state). Approbation of the digitalization index of interaction between the state and citizens in the regional context was carried out. To assess the applicability of the proposed index, the correlation dependence of its values and the values of the index components on the level of education of the population, employment, income and urbanization, as well as differences in the availability of information and communication technologies infrastructure was investigated. At the same time, the level of digitalization correlation of interaction between the state and citizens with social factors is higher than with infrastructural ones. This means that to solve the problem of digital inequality in Russian regions, it is not enough to provide universal access to the Internet; factors of human capital development also play an important role in promoting digital channels of interaction. Conclusion. Assessing the digitalization of interaction between the state and citizens requires taking into account various indicators that reflect the immediate, intermediate and final results of such an interaction, as well as the risks associated with the transition to “digit”. In terms of the provision of public services for such an assessment, it is advisable to use the digitalization index of interaction between the state and citizens. Further promising areas of research in the field of assessing the digitalization of interaction between the state and citizens are related to the study of the influence of citizens’ trust in government bodies on the level of digitalization of interaction between the state and citizens, as well as taking into account the interaction of citizens and the state within the framework of other types of state functions (development and implementation of state policy, regulation, control and supervisory activities). The implementation of these directions will require the expansion of the currently available information base.